At a crossroads: Uber and the ambiguities of the COVID-19 emergency in Lisbon. (1st January 2021) - Allegretti, Giovanni; Holz, Sheila; Rodrigues, Nuno
Abstract : The emergence of the COVID-19 pandemic has brought to the surface some problems and trends within digital platforms, including working conditions, while simultaneously transforming the relationship between platform capitalism and the pandemic complex. Through the case analysis of Uber in Lisbon, we were able to identify a situation where several ambiguities emerged, some of which are associated with the Portuguese singularity of intermediary platform capitalism. From this analysis, anchored to several interviews with Uber drivers/partners, we observed that the pandemic crisis has aggravated some inequalities and problems generally associated with platform capitalism, but also seen new trends and solutions emerge for a political and socio-economic reformulation of this sector.